Oceanic and Atmospheric Correlations to Cetacean Mass Stranding Events in Cape Cod, Massachusetts, USA - R. Zellar; A. Pulkkinen; K. Moore; C. S. Rousseaux; D. Reeb (Geophysical Research Letters)
Abstract Groups of pelagic dolphins and whales (order Cetacea) regularly strand on beaches throughout the world. These strandings are referred to as mass stranding events (MSEs). MSEs have been observed for centuries, however the underlying causes remain unclear. In Cape Cod, Massachusetts, USA, MSEs usually involve only a few species of cetaceans. We investigated possible connections between MSEs in Cape Cod and regional wind and ocean currents. The seasonal MSE distribution is strongly correlated to both wind and ocean current strengths, and correlation is maximized when MSEs are compared to environmental data one month in the past. Furthermore, a superposed epoch analysis (a Chree analysis) indicates significant shifts in ocean current strength for months surrounding MSEs. These results may indicate that atmospheric and oceanic effects are possible underlying factors influencing MSEs. These factors could generate environments conducive for prey assemblages that attract cetaceans, or perhaps by driving seasonal production of prey species.